Allicin attenuates tunicamycin-induced cognitive deficits in rats via its synaptic plasticity regulatory activity - Xiang, Qiong (Iran J Basic Med Sci, 2017)
OBJECTIVE(S): To illuminate the functional effects of allicin on rats with cognitive deficits induced by tunicamycin (TM) and the molecular mechanism of this process. MATERIALS AND METHODS: 200–250 g male SD rats were divided into three groups at random: control group (n=12), TM group (5 μl, 50 μM, ICV, n=12), and allicin treatment group (180 mg/kg/d with chow diet, n=12). After 16 weeks of allicin treatment, the learning ability and memory were tested using novel object recognition (NOR) testing on rats with 72 hr TM treatment (5 μl, 50 μM, ICV); meanwhile, the variation of field excitatory postsynaptic potential (fEPSP) in the Schaffer Collateral (SC)-CA1 synapse was detected by extracellular electrophysiological recordings and the morphology of dendritic spine was observed by Golgi staining as well as detecting several synaptic plasticity-related proteins by Western blot. RESULTS: The density of dendritic spine was increased significantly in allicin-treated groups and the correspondence slope of fEPSP in TM-induced cognitive deficits group was enhanced and expression of synaptophysin and glutamate receptor-1(GluR1) in hippocampal neurons was up-regulated. CONCLUSION: The results indicate that allicin plays an important role in synaptic plasticity regulation. These finding showed that allicin could be used as a pharmacologic treatment in TM-induced cognitive deficits.